STATE CAPACITY AND DEVELOPMENT PERFORMANCE IN NIGERIA: A COMPARATIVE ANALYSIS OF SUBNATIONAL GOVERNMENTS - OKACHI Tochi (Proceeding of International Conference on Social Science and Humanity, 2026)
Objective: This paper has discussed how state capacity affects the performance of development in the subnational governments in Nigeria based on the Weberian Bureaucratic Theory and the Institutional Theory by North. Method: Based on a descriptive qualitative research design and content analysis, the study examined the influence of administrative, fiscal, and regulatory capabilities on socio-economic outcomes in a selected set of states. Results: The results showed that those states that had integrated administrative professionalism, fiscal autonomy and effective regulatory enforcement continued to record better development outcomes in education, healthcare, infrastructure and human development. Conversely, states with weak bureaucracies, financial reliance and ineffective regulatory frameworks had low performance even when they had the same endowments of resources. The research also determined that the relationship between state capacity and development performance is mediated by leadership quality, strategic planning and institutional coordination. The paper has found that the effectiveness, coherence, and integration of state capacities rather than availability of resources are the key determinants of development performance in Nigeria. It underlined that the key drivers of sustainable development at the subnational level are strong institutions, not the availability of resources. Novelty: The study based on these findings suggested that subnational governments ought to focus on merit-based recruitment and on-going capacity-building in the civil service, to build internally generated revenue sources to promote fiscal independence, and to strengthen regulatory frameworks to implement policies effectively. It also emphasised the importance of steady leadership, strategic planning over the long term and increased intergovernmental cooperation to maximize the governance performance and decrease development inequalities among the states in Nigeria.